Applying quality to R&D means 'Learn-As-You-Go' - Eidt, Clarence M. Jr (Research management (Now: research technology management))
Clarence M. Eidt, Jr. relates how Exxon Research and Engineering Co. has obtained a continuous improvement in its R&D performance by applying the principles of quality management.